Mutations compensating for the fitness cost of rifampicin resistance in Escherichia coli exert pleiotropic effect on RNA polymerase catalysis. Issue 10 (26th May 2022) - Kurepina, Natalia; Chudaev, Maxim; Kreiswirth, Barry N; Nikiforov, Vadim; Mustaev, Arkady
Abstract: The spread of drug-resistant bacteria represents one of the most significant medical problems of our time. Bacterial fitness loss associated with drug resistance can be counteracted by acquisition of secondary mutations, thereby enhancing the virulence of such bacteria. Antibiotic rifampicin (Rif) targets cellular RNA polymerase (RNAP). It is potent broad spectrum drug used for treatment of bacterial infections. We have investigated the compensatory mechanism of the secondary mutations alleviating Rif resistance (Rif r ) on biochemical, structural and fitness indices. We find that substitutions in RNAP genes compensating for the growth defect caused by βQ513P and βT563P Rif r mutations significantly enhanced bacterial relative growth rate. By assaying RNAP purified from these strains, we show that compensatory mutations directly stimulated basal transcriptional machinery (2–9-fold) significantly improving promoter clearance step of the transcription pathway as well as elongation rate. Molecular modeling suggests that compensatory mutations affect transcript retention, substrate loading, and nucleotidyl transfer catalysis. Strikingly, one of the identified compensatory substitutions represents mutation conferring rifampicin resistance on its own. This finding reveals an evolutionary process that creates more virulent species by simultaneously improving the fitness and augmenting bacterial drug resistance. Graphical Abstract: